(untitled) (Research, Society and Development, 2022)
The microalgae Chlorella vulgaris is usually commercialized as nutraceutical although it has potential application in the pharmaceutical and cosmetic industries. Therefore, our objective in this research is to evaluate the mutagenic and antimutagenic action of the aqueous extract of C. vulgaris through the Allium cepa assay. Three concentrations of the aqueous extract of C. vulgaris were tested: 0.075, 0.15 and 0.30mg/mL. In the mutagenicity analysis, A. cepa meristematic cells were cultured in the presence of the aqueous extract of C. vulgaris with distilled water as negative control and copper sulfate as positive control. For antimutagenicity, pre-treatment, simple simultaneous and post-treatment protocols were used. 400 cells/treatment were analyzed under optical microscopy (40x). Data were analyzed by ANOVA (one-way) and Tukey tests, considering p<0.05. The aqueous extract of C. vulgaris did not show mutagenicity in any of the three concentrations evaluated. About the antimutagenicity protocols, the harm reduction percentages were 94.7%, 94.1% and 96.2% (pre-treatment); 88.9%, 93.2% and 91.08% (simultaneous simple); and 85.2%, 84.5% and 94.7% (post-treatment) referring to concentrations of 0.075, 0.15 and 0.30 mg/mL, respectively. According to these results, the microalgae C. vulgaris did not show mutagenic action at the tested doses and it reduced genetic damage caused by copper sulfate.